GAYA BAHASA NOVEL SANG PEMIMPI KARYA ANDREA HIRATA DALAM PEMBELAJARAN BAHASA INDONESIA TENTANG GAYA BAHASA DI SMA KELAS X - Syarif Faqihuddin; Evi Chamalah; Leli Nisfi Setiana (Jurnal Pendidikan Bahasa Indonesia, 2017)
This research takes the novel Sang Pemimpi by Andrea Hirata as the basicreference of the study of the style of language as a class X learning at the level of high school. The problem studied in this research is to analyze the language style contained in novel Sang Pemimpi by Andrea Hirata in learning of Indonesian class X in high school level. This study aims to determine the style of language in the novel Sang Pemimpi by Andrea Hirata in learning the language and Indonesian Literature in high school students of class X. In this study, the method used is qualitative method. The application of this qualitative method is descriptive, which means the data produced in the form of words in the form of quotations. The data in this research is exposure of the language (written text), ie words, phrases, sentences contained elements of the language style contained in the novel Sang Pemimpi by Andrea Hirata. Stages of this research is data collection, selection of data,Â  analyzing data that has been selected, and make research reports. This research is expected to be an alternative of literary learning especially on the style of language in SMA level.